Gamifikasi sebagai Strategi Edukatif dalam Mengurangi Ketergantungan Gadget Siswa di Era Digital - Ubaidillah, Ahmad (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This study explores gamification as an educational strategy to reduce students' dependence on gadgets in the digital age. This research used a descriptive qualitative approach through classroom observations and interviews at SMPN 1 Waru. The study revealed that conventional teaching often triggered students' requests to use gadgets, while gamified learning significantly diverted their attention from gadgets. The findings showed that 5 out of 6 sessions observed using traditional methods resulted in high gadget requests, while gamified sessions eliminated such requests completely. Students reported increased engagement and enjoyment in gamified activities, which is stated. This study highlights the dual role of gamification: reducing excessive gadget use while increasing motivation. This study contributes to digital age pedagogy by proposing non-digital gamification as a new solution to balance technology integration and focused learning.